PENYULUHAN KESEHATAN GIGI DAN MULUT SERTA EDUKASI SIKAT GIGI DAN KURATIF SEDERHANA PADA SISWA SEKOLAH DASAR ALWAHLIYAH MARTUBUNG - Sekar Restuning; Yenni Lisbeth Siahaan; Dumamey Siahaan; Sutriatai Sutriatai (Poltekkes Kemenkes Bandung, 2022)
Prevention of dental caries in the community can be done by providing counseling on how to brush your teeth properly and the dangers of dental caries. In addition, the joint toothbrush program in schools can also be carried out to get children used to brushing their teeth regularly and properly. Caries disease in children occurs a lot and often occurs due to lack of attention from parents because it is assumed that the child's teeth will be replaced by permanent teeth. Parents do not realize that the actual impact will be very large if treatment is not carried out to prevent dental caries from an early age in children. The purpose of this community service is to increase children's knowledge about dental and oral health, so that they can prevent dental caries in children by providing counseling and education on tooth brushing together. Observation of children can understand how to maintain healthy teeth and mouth by demonstrating how to brush their teeth together. During the three times the implementation of community service in the form of counseling in each different group, it was seen that there was an increase in children's knowledge.